2009
DOI: 10.1002/ejsp.503
|View full text |Cite
|
Sign up to set email alerts
|

‘Our way of life is worth defending’: testing a model of attitudes towards superordinate group membership through a study of Scots' attitudes towards Britain

Abstract: This research used a survey design (N ¼ 227) to investigate Scottish people's support or opposition to independence from Britain. It was hypothesised that political attitudes towards supra-national bodies are not a direct function of the degree of ingroup (Scottish) identification, but are moderated by the extent to which the expression of ingroup identity is seen as being undermined within the larger entity. This feeling of identity undermining is assumed to arise from perceptions of incompatibility with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(94 citation statements)
references
References 29 publications
5
89
0
Order By: Relevance
“…independence, but because it is unusual to support independence without identifying as a Scot -see Sindic & Reicher, 2007), it had no direct effect on RIP even with support for independence removed from the regression model (β = -.072, p = .557), thus violating one of the conditions for mediation (Barron & Kenny, 1986), whether Scottish identification is considered as the mediator or as the mediated variable.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
See 2 more Smart Citations
“…independence, but because it is unusual to support independence without identifying as a Scot -see Sindic & Reicher, 2007), it had no direct effect on RIP even with support for independence removed from the regression model (β = -.072, p = .557), thus violating one of the conditions for mediation (Barron & Kenny, 1986), whether Scottish identification is considered as the mediator or as the mediated variable.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…The key difference is that, whereas RCT predefines that which constitutes 'interest' in material terms, we argue that the definition of interest depends upon the definition of the group identity and upon identityrelated motivations (Sonnenberg, 2003). In the particular case of Scottish identity, those who argue for or against independence do so around the question of how it will impact on the Scottish way of life (Sindic & Reicher, 2007). Certainly, there are those who argue for independence on economic grounds, but they do so on the underlying basis that wealth will improve the ability of Scots to preserve their identity-based values and practices (Sindic, 2005 (Marr, 1992).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Using Social Identity Theory (SIT: Tajfel & Turner, 1986), Sindic and Reicher (1999) proposed a novel concept of intergroup threat termed identity undermining. The authors defined identity undermining as a threat deriving from the inability of group members to fully enact and express the norms, values and practices characteristic of their given group's social identity.…”
Section: Group Incompatibilitymentioning
confidence: 99%
“…In addition, threats to group identity make people turn to the minority ingroup that provides a sense of belongingness and inclusion that enhances positive self-feelings (Leary & Baumeister, 2000). Research has found strong associations between the feeling of identity undermining and ingroup identification (Brug & Verkuyten, 2007;Sindic & Reicher, 2009). Thus, situational threats can be expected to make ethnic identity more salient and thereby more relevant for well-being.…”
Section: Assimilation and Well-beingmentioning
confidence: 99%